Are there differences in the kinetic parameters of the vertical jump on different types of sand performed by beach volleyball players? - Oliveira Neto, Francisco de (2024)
Vertical jumps are frequently used to measure neuromuscular capacity, with countermovement jumping (CMJ) and squat jumping (SJ) which are the types of jumps most commonly used by researchers. To better understand how force manifests, force-time curve analysis has been further explored. It is known that kinetic parameters of jumps performed on hard surfaces behave differently from those performed on sand. Even though there is an indication from the International Volleyball Federation, it is common to see athletes training in different types of sand with different density levels. The purpose of this study was to assess the kinetic variables of the vertical jump performed by beach volleyball athletes on sands with different particle size distributions. We evaluated 432 jumps (216 SJ; 216 WYD), performed by 12 athletes ((age = 23.5 ± 5.8 years, height = 175.4 ± 5.0 cm, body mass = 67.0 ± 4.8 kg, years of practice = 8.2 ± 4.4 years) who regularly train and compete at national and international level, including Pan american champions, world champions and under-21 national champions. Data was collected in a laboratory environment, where three types of sand were placed inside trapezoidal wooden boxes (lower base dimensions: 46 x 50 cm; upper opening dimensions: 59 x 63 cm; depth: 40 cm) and these were positioned in random order above a force platform for the jumps. Samples of the sands were sent to the soil analysis laboratory of the Federal University of Ceará, where they underwent analysis of the size and distribution of the particles using chemical methods (sodium hexametaphosphate) and physical methods (rapid stirring for 10 min) and the amount of clay was quantified by the pipetting method. Data acquisition was performed using a force platform (Bertec model FP4060-08-1000, COLUMBUS, OH, USA, sampling frequency of 1000 Hz.) and analysis by the Matlab routine (The MathWorks Inc., Natick, MA, USA) The omnibus test in SJ models showed differences among granulometry, only for time variables. The post-hoc analyzed revealed higher values for total duration in sand 1 than sand 2, time to peak power in sand 1 showed higher values than sand 2 and 3. For CMJ model, total duration (sand 1 higher than sand 3), eccentric phase duration (sand 1 and 2 higher than sand 3), concentric phase duration (sand 3 higher than sand 1), time to peak power (sand 1 higher than sand 2 and 3), time to peak force (sand 2 higher than sand 3), max rate force development concentric phase (sand 2 and 3 higher than sand 1), maximum velocity (sand 3 higher than sand 2) and peak power eccentric (sand 3 higher than sand 2). The particle size distribution influenced the neuromuscular function and, therefore, the generation of strength. This information is important so that athletes and coaches can reflect on their practice and build training strategies that consider the density of the sand where they train or play.